Impaired virus‐specific T cell responses in patients with myeloproliferative neoplasms treated with ruxolitinib. Issue 4 (22nd July 2020) - Rumi, Elisa; Sant'Antonio, Emanuela; Cavalloni, Chiara; Comolli, Giuditta; Ferretti, Virginia Valeria; Cassaniti, Irene; Pietra, Daniela; Trotti, Chiara; Ciboddo, Michele; Furione, Milena; Vanni, Daniele; Casetti, Ilaria Carola; et al.
Abstract: Ruxolitinib is effective in myeloproliferative neoplasms (MPN) but can cause reactivation of silent infections. We aimed at evaluating viral load and T‐cell responses to human cytomegalovirus (HCMV) and Epstein‐Barr virus (EBV) in a cohort of 25 MPN patients treated with ruxolitinib. EBV‐DNA and HCMV‐DNA were quantified monthly using real‐time polimerase chain reaction (PCR) on peripheral blood samples, and T‐cell subsets were analyzed by flowcytometry. HCMV and EBV‐directed T‐cell responses were evaluated using the IFN‐γ ELISPOT assay. Most patients had CD4+ and/or CD8+ T‐cells below the normal range; these reductions were related to the duration of ruxolitinib treatment. In fact, reduced T‐lymphocytes' subsets were found in 93% of patients treated for ≥5 years and in 45% of those treated for <5 years ( P = .021). The former also had lower median numbers of CD4+ and CD8+ cells. Subclinical reactivation of EBV and HCMV occurred in 76% and 8% of patients. We observed a trend to an inverse relationship between EBV and CMV‐specific CD4+ and CD8+ T‐cell responses and viral load, and a trend to an inverse correlation with ruxolitinib dose. Therefore, our data suggest that the ruxolitinib treatment may interfere with immunosurveillance against EBV and HCMV.